Macrophage-induced lymphangiogenesis and metastasis following paclitaxel chemotherapy is regulated by VEGFR3 - Alishekevitz, Dror; Scherer, Sandra; Sleeman, Jonathan P. (Cell reports, 2016)
Summary - While chemotherapy strongly restricts or reverses tumor growth, the response of host tissue to therapy can counteract its anti-tumor activity by promoting tumor re-growth and/or metastases, thus limiting therapeutic efficacy. Here, we show that vascular endothelial growth factor receptor 3 (VEGFR3)-expressing macrophages infiltrating chemotherapy-treated tumors play a significant role in metastasis. They do so in part by inducing lymphangiogenesis as a result of cathepsin release, leading to VEGF-C upregulation by heparanase. We found that macrophages from chemotherapy-treated mice are sufficient to trigger lymphatic vessel activity and structure in naive tumors in a VEGFR3-dependent manner. Blocking VEGF-C/VEGFR3 axis inhibits the activity of chemotherapy-educated macrophages, leading to reduced lymphangiogenesis in treated tumors. Overall, our results suggest that disrupting the VEGF-C/VEGFR3 axis not only directly inhibits lymphangiogenesis but also blocks the pro-metastatic activity of macrophages in chemotherapy-treated mice.
Gesehen am 26.06.2019